Multimodal approach towards understanding the changes in the autonomic nervous system induced by an ultramarathon. Issue 2 (2nd April 2020) - Vieluf, Solveig; Scheer, Volker; Hasija, Tanuj; Schreier, Peter J.; Reinsberger, Claus
ABSTRACT: Purpose : Running an ultramarathon can be considered as a multifaceted, intense stressor inducing changes within the autonomic nervous system (ANS). The aim of this study was to examine changes within and across ANS modalities in response to an ultramarathon. Methods : Thirteen runners (44.3 ± 5.9 years) completed a 65 km run. Electrodermal activity (EDA), heart rate (HR), and skin temperature measured at wrist (Temp), were recorded before and after running. Three-minute intervals were analysed. Mean values were compared by t-tests for dependent samples. Joint principal component analysis-canonical correlation analysis (PCA-CCA) and multiset CCA techniques were employed to measure the interactions between either any two or among all modalities. Results : HR (p < 0.01) and EDA (p < 0.01) increased, while Temp decreased (p < 0.01). PCA-CCA revealed one significant component (p < 0.05) for each modality pair in pre and post measures. Component strength increased from pre (mean = 0.73) to post (mean = 0.92) test. Multiset CCA supported the assumption of increasing strength of correlations across modalities. Conclusion : Ultramarathon, an intense physical stressor, increases correlations across modalities pointing towards a reorganization of central ANS control to restore dynamic balance after physical load. This characterization of ANS-states might offer new avenues for training control.